Multiple Indicators of Violence Against Female Sex Workers And Its Associated Factors in Ghana: Evidence from the 2015 Integrated Bio‐Behavioral Surveillance Survey Cross‐Sectional Study - Ayamah, P.; Aheto, J.M.K; et al. (Wiley Periodicals LLC, 2023)
Background and Aims: Violence against female sex workers (FSWs) is a widespread phenomenon, especially in African nations like Ghana where sex work is outlawed primarily because of the pervasive worldview that sex work is a contravention of morality. Violence against FSWs deters them from accessing critical health services and heightens their risk of STIs including HIV infection. The study examined the prevalence and the associated factors of multiple indicators of violence against FSWs. Methods: The study utilized a cross‐sectional secondary data from the 2015 Integrated Bio‐Behavioral Surveillance Survey conducted among FSWs and their nonpaying partners by Ghana AIDS Commission. We analysed data on a total of 4279 participants. Bivariate, and multivariable logistic regression analyses were utilized to identify factors associated with physical and sexual violence against FSWs. Data were analysed using Stata version 15. Results: Of the 4279 FSWs, 433 (10%) and 1059 (25%) suffered physical and sexual violence, respectively. The predictors of physical violence are being a seater (adjusted odds ratio [aOR] = 0.53, 95% confidence interval [CI]: 0.36–0.74), aged ≥40 (aOR = 0.23, 95% CI: 0.08–0.64), nonuse of drugs (aOR = 0.56, 95% CI: 0.44–0.70), not using alcohol before sex (aOR = 0.69, 95% CI: 0.56–0.86) and petty business (aOR = 1.39, 95% CI: 1.05–1.82). Sexual violence was predicted by those aged 31–40 (aOR = 0.68, 95% CI: 0.49–0.94) and age ≥40 (aOR = 0.38, 95% CI: 0.22–0.66), currently married (aOR = 0.42, 95% CI: 0.27–0.67), having no living children (aOR = 0.69, 95% CI: 0.51–0.94), nonuse of drugs (aOR = 0.80, 95% CI:0.68–0.94), and not using alcohol before sex (aOR = 0.74, 95% CI: 0.63–0.86). Region was associated with both physical and sexual violence. Both physical and sexual violence had negative consequences on consistency of condom use and condom failure among FSWs. Conclusion: Physical and sexual violence against FSWs is pervasive, and a critical public health issue in Ghana. The identified associated factors could be considered as part of an overall strategy aimed at addressing the menace.
Research Article
Keywords: clients and partners; commercial sex workers; female sex workers; HIV/AIDS